Effect of dietary supplementation of L-carnitine on growth, feed utilisation and liver histology in Nile tilapia Oreochromis niloticus (Linnaeus, 1758) fry - Erdogan, F.; KanyÄ±lmaz, M.; AydÄ±n, B.; Erdogan, M.; Aksoy, A.; Gumus, E. (Indian Journal of Fisheries, 2015)
This study was undertaken to investigate the effect of dietary supplementation of L-carnitine on the growth performance and liver histology in fry of Nile tilapia, Oreochromis niloticus. Five isonitrogenous and isolipidic experimental diets were formulated to contain 0 (control), 250, 500, 750 and 1000 mg L-carnitine kg-1, respectively. Fish were randomly distributed in groups of 20 fish per 120 l glass aquaria and fed the diets three times daily to apparent satiation in triplicate for 120 days. Final body weight, specific growth rate, feed conversion ratio, protein efficiency ratio, feed intake and whole body composition for fish fed with diets containing different levels of L-carnitine were not significantly different compared to fish fed the control diet. Fish exhibited normal liver histological structure. However, there was a comparatively low hepatic fat acumulation with increase in dietary L-carnitine supplementation. Results indicated that supplemental dietary L-carnitine had no beneficial effect on improving growth performance, feed utilisation and body composition of Nile tilapia fry.